Delo Franceta Bevka v luči literarne zgodovine in srednješolskih beril - Božič, Zoran (Jezik in slovstvo, 2014)
The article presents a literary-historical view of the role and significance of France Bevk's literature by comparing it with the author's role in secondary school reading materials. Seeking parallels with the literary-historical and schooling situations of Ivan Pregelj and Ciril Kosmač, the comparison is focused on the post-World War II period. While Bevk's literary-historical position in the interwar period was preserved largely due to his role in building national awareness, after Slovenia's independence, he became a somewhat marginalised secondary school author. The only text (optionally) treated in secondary school reading texts is Bevk's novel Kaplan Martin Čedermac.
Keywords: France, Bevk, 1890-1970; Kosmač, Ciril, 1910-1980; Pregelj, Ivan, 1883-1960; slovenski pisatelji; literarna zgodovina; history of literature; srednješolska berila; kanonizacija; recepcija; didactic method; didaktika